Experimental methods in survey research : techniques that combine random sampling with random assignment /: techniques that combine random sampling with random assignment. (2019) - Lavrakas, Paul J; Traugott, Michael W; Leeuw, Edith Desirée de; Kennedy, Courtney; Holbrook, Allyson L
No abstract available